Potential of Bone-Marrow-Derived Mesenchymal Stem Cells for Maxillofacial and Periodontal Regeneration: A Narrative Review - Hamid Reza Khorasani; Mahboubeh Sanchouli; Javad Mehrani; Davood Sabour (Hindawi Limited, 2021)
Bone-marrow-derived mesenchymal stem cells (BM-MSCs) are one of the most widely studied postnatal stem cell populations and are considered to utilize more frequently in cell-based therapy and cancer. These types of stem cells can undergo multilineage differentiation including blood cells, cardiac cells, and osteogenic cells differentiation, thus providing an alternative source of mesenchymal stem cells (MSCs) for tissue engineering and personalized medicine. Despite the ability to reprogram human adult somatic cells to induced pluripotent stem cells (iPSCs) in culture which provided a great opportunity and opened the new door for establishing the in vitro disease modeling and generating an unlimited source for cell base therapy, using MSCs for regeneration purposes still have a great chance to cure diseases. In this review, we discuss the important issues in MSCs biology including the origin and functions of MSCs and their application for craniofacial and periodontal tissue regeneration, discuss the potential and clinical applications of this type of stem cells in differentiation to maxillofacial bone and cartilage in vitro, and address important future hopes and challenges in this field.